Optimization of algorithms transferring numeric positional codes for discrete channels with the fluctuation noise - Sergey Gennad'yevich Rassomahin; Oleg Pavlovich Malofey; Aleksandr Olegovich Malofey (Наука. Инновации. Технологии)
The article suggests algorithm for generating and processing signals for transmission of positional codes, based on the criterion of minimum mean squared error recovery numbers on the output channel with additive white Gaussian noise (AWGN). The algorithm enables the use of non-uniform energy «protection» of numbers by combining bits of «soft» and «hard» decisions in the best reception conditions limit the average power of the transmitter. For a different channel quality parameters calculated signals and indicators of efficiency of the algorithm. The pos-sibility of achieving a significant gain in accuracy transmit positional numbers are achieved without additional frequency and energy costs.